ANALISIS STRUKTUR FISIK DAN BATIN PUISI KARYA SISWA KELAS X SMAN 8 DENPASAR DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Putu Dessy Fridayanthi; Ida Ayu Agung Ekasriadi (Widyadari, 2025)
Poetry is the result of expressing feelings and inner experiences that are poured out through distinctive and imaginative word choices. This study aims to analyze the physical structure and inner structure of poetry by class X students of SMA Negeri 8 Denpasar in an effort to improve Indonesian language learning outcomes. The subjects of the study were class X students in the 2024/2025 academic year. This study uses a descriptive qualitative approach to obtain in-depth and meaningful data. The data sources used consist of primary and secondary sources, with data collection techniques through documentation and literature studies. Data analysis techniques include reading and taking notes on the poems that have been collected by students, then analyzed based on elements of physical structure (diction, imagination, style, rhyme, and facial expression) and inner structure (theme, tone, feelings, and messages). The results of the study show that the diction used by students tends to use everyday language; imagination is dominated by visual images and feelings; the style of language used includes metaphor, personification, and hyperbole. The most frequently raised theme is romance, with the tone of poetry varying between melancholic, romantic, and cynical. The feelings depicted in the poem are love and despair, while the message is generally conveyed explicitly. This finding shows that the use of student-written poems can be used as an effective learning medium to improve literary appreciation and Indonesian language learning outcomes.